Enhanced flame retardant polymer nanocomposites - Elbasuney, Sherif (2013)
Fire is a continuous threat to life and property. The total annual UK fire loss is estimated to be 0.25% of its gross domestic product (GDP) (Goddard, 1995). According to fire statistics, more than 12 million fires break out every year in the United States, Europe, Russia, and China killing about 166,000 people and injuring several hundreds of thousands (Morgan and Wilkie, 2007). Polymers which take up 80% of the organic chemical industry, are known for their high flammability with the production of heat, corrosive toxic gases, and smoke (Bent, 2010). Improving the fire retardancy of polymeric materials is a major concern and also a major challenge. Nanotechnology could have a significant impact on polymeric materials through the achievement of polymer nanocomposites (PNs) with enhanced functional properties (Giannelis, 1996, Schartel and Batholmai, 2006). If this can be achieved, there will be an enormous increase in the use of improved flame retardant (FR) PNs in mass transportation, aerospace, and military applications where fire safety will be of utmost importance (Horrocks and Price, 2008).